(untitled) (KULT_online, 2018)
In what ways have historians in both German states dealt with the history of colonial Namibia? Which continuities become evident within the historiographies of the GDR and the FRG, specifically regarding (post-)colonial epistemologies? These questions are addressed by Christiane Bürger in Deutsche Kolonialgeschichte(n), in which she reconstructs the dynamic and challenging history of the colonial historiography after the Second World War. Her focus is on the various and varying interpretations of imperial Germany’s colonial genocide com-mitted against the Herero and Nama (1904 to 1908). Based on an analysis of diverse texts and media she shows how academic and popular traditions of knowledge have circulated and transformed across disciplinary, epochal, and national borders.